THE STUDY OF STRESS-STRAIN STATE OF THE DISTILLATION PROCESSING OF THE TUNNEL WITH THE ACCOUNT OF TECHNOLOGICAL PROCESSES - Tiutkin, O. L. (Science and Transport Progress, 2008)
The results of mathematical simulation for process of assembling the sectional casing during heading works are presented in the paper. The finite-element model of wayside is developed, in which it is possible to represent the influence of hydraulic cylinders of a heading machine on the casing and the results of simulation of such a case are analysed.